Factor Shares, Redistribution and Growth in a Captured Democracy - Andrea Vindigni (Institute of Labor Economics (IZA), 2024)
A model of endogenous growth is presented, based on productive public expenditures, and featuring some degree of income inequality, and polarization in policy preferences. The main innovation lays in the political process determining capital taxation that relies, both on voting and on "influence activities," exploited by the capitalist elite in order to capture some political power at the expenses of the median voter. In particular, investments in lobbying activities allow the rich to obtain lower capital taxes, to the benefit of both themselves and economic growth. The model's equilibrium dynamics features variable taxes and lobbying. In addition, it is established the existence of a transitional dynamics featuring convergence to a balanced growth path, characterized by constant taxes and lobbying (and a constant growth rate of consumption and capital). Capital accumulation leads, along the transitional path, to more and more lobbying, that asymptotically cause taxation to reach precisely the tax rate preferred by the capitalists (induced by a very large political pressure on the government). Specifically, the (unique) balanced growth equilibrium features the maximization of the net interest rate, as well as the economy's growth rate and capitalists' welfare. On the transitional path, lobbying reduces the workers' political weight (and their consumption), and therefore makes fiscal policy relatively more and more capitalists friendly. Policy polarization (loosely speaking reflecting inequality) has somewhat interesting effects along the transitional path towards balanced growth. Hereby, actual taxes become more capitalists-friendly relatively to the Meltzer and Richard's (1981) canonical median voter tax benchmark, mutatis mutandis. In the end, full convergence is established, from a pure democracy ruled through the de jure power only, to a political economic realm totally de facto dominated by the few capitalists, i.e. to an "oligarchic technocracy," possibly ruled by the "top 1%" of the population.
Keywords: O11; O43; 330; political economy; government; inequality; economic growth; redistribution; lobbying